PENGEMBANGAN BAHAN AJAR INSYA’ BAGI PESERTA DIDIK DI MADRASAH TSANAWIYAH SULTAN HASANUDDIN KABUPATEN GOWA - Aziz, Abdil Mubarak (Pascasarjana IAIN Sorong, 2023)
The aim of this research is to describe the steps for developing Insya' teaching materials at Madrasah Tsanawiyah Sultan Hasanuddin. The steps for developing Insya' teaching materials are based on the steps developed by Sugiyono from Borg & Gall, namely: (1) Potential and problems; (2) Collect information and data; (3) Product design; (4) Design validation; (5) Design revision; (6) Product testing; (7) Product revision; The implications of this research and development are 1) This research and development has produced Insya' teaching material products. This product has been tested through several tests, namely testing by language experts and design experts and also tested on class VII students at MTs. Sultan Hasanuddin to prove the effectiveness of the product being developed, so that it can be a consideration for educators, especially subject teachers, Insya>' to use this product. 2) This research still has many limitations and shortcomings in designing teaching materials. Insya', this will become reference material for designing more creative and innovative teaching materials to be developed. 3) The materials included in the Insya' teaching materials are still limited to only 14 materials and only for class VII, this is due to researchers' limitations in compiling and presenting the material. This will be taken into consideration for further research to improve Insya' teaching materials for a higher level